Combining Acmella oleracea and Boswellia serrata extracts: a novel pharmacological approach in inflammatory vestibulodynia - Fusco, Antimo; Perrone, Michela; Ricciardi, Federica; Morace, Andrea Maria; Bonsale, Roozbe; Teweldemedhin, Milena Melake; Di Martino, Emanuele; Limongelli, Rebecca; Papa, Alfonso; Maione, Sabatino; Guida, Francesca; Luongo, Livio (Frontiers in Pharmacology, 2024)
Vulvodynia is a chronic pain condition that affects the vulvar area, often resulting in significant discomfort and a reduced quality of life. Current treatments for vulvodynia are limited, and there is a need for more effective therapeutic options. Acmella oleracea, known for its spilanthol content, and Boswellia serrata, rich in boswellic acids, have been explored for their potential analgesic properties in pain management. In this study, vulvodynia-like symptoms were induced in female mice using Complete Freund's adjuvant (CFA). After the induction of symptoms, the mice were treated with a combination of Acmella oleracea and Boswellia serrata extracts (AO+BA). Behavioral pain assessments were conducted to monitor the effects of the treatment. Additionally, biochemical and functional evaluations were performed to measure spinal microgliosis and neuronal overexcitation.The combination of Acmella oleracea and Boswellia serrata (AO+BA) resulted in a significant reduction of vulvar hypersensitivity in mice. Besides alleviating pain, AO+BA therapy also reduced spinal microgliosis and neuronal overexcitation in mice with vulvodynia. The findings suggest that the AO+BA combination has the potential to alleviate vulvodynia associated pain through mechanisms involving the reduction of spinal microgliosis and neuronal overexcitation. These results point to the therapeutic promise of these plant extracts for chronic pain conditions like vulvodynia.The combination of Acmella oleracea and Boswellia serrata shows potential as a treatment for vulvodynia. However, further studies are needed to explore the underlying mechanisms and to optimize the dosage for clinical use.